The Theory of Epistemic (In)Justice in the Perspective of the Performance of Law: An Approach Based On The Concept Of Hermeneutic Therapy - Mariola Żak (Acta Universitatis Lodziensis Folia Iuridica)
In this paper, the assumptions of Miranda Fricker’s theory of epistemic (in)justice read in the context of the neo-Wittgensteinian philosophical trend, also called therapeutic or resolute approach, will be approximated. The theory in question concerns the issue of unequal participation of the experiences of specific marginalised individuals or their groups in the practices of legal meaning-making. The aim of the paper is to show the role of the said theory in legal theory. In the first step, I will discuss the main assumptions of the theory of epistemic (in)justice and its varieties from the perspective of the lawyer-layperson epistemic dependence. I will also present normative proposals for implementing the ideal of epistemic justice as well as a justification for abandoning such a research approach. In the second step, I will show an alternative to normative approaches in the form of a theoretical innovation consisting in supplementing the assumptions of the epistemic (in)justice theory with a therapeutic-resolute reading of the late Wittgenstein in the hermeneutic perspective. In the third step, I will demonstrate that the full application of the theoretical innovation presented in the previous steps within legal institutions requires taking into account the critical category of legal imagination related to “playing” or the performance of law (the game activity) in the sense of performance studies. The fourth step will be to identify sensitive legal institutions that can be improved by including the categories proposed by the theory in question while taking into account the concept of hermeneutic therapy derived from Type III deliberation. In order to illustrate the application possibilities of the theory of epistemic (in)justice in the area of law, I will use a case study. I will apply the following methods: analytical, thick description, and critical legal studies with elements of feminist research methodology.